Media Evangelisasi Kaum Muda Gereja Antonius Kotabaru Yogyakarta dari Masa ke Masa - Nadyaningtyas, Beatricia Adinda (Sekolah Tinggi Teologi Tenggarong, 2024)
Abstract:The digitalization of services provided by the younger generation has now spread to various social media platforms which are the focus of the research in this article. Current developments have a strong influence on the dissemination of information to Catholics in Yogyakarta, especially the St. Antonius Padua Kotabaru Yogyakarta and its surroundings. The increasing development of new media that has become a reality due to the internet has also had an impact not only on the younger generation but also on children and adults who can access this new media. Therefore, there are deep implications in bringing the Church's ministry mission or evangelization into the digital era. This research aims to examine the importance of the new media transformation that occurred at the Santo Antonius Padua Parish Church, Kotabaru Yogyakarta, which has the slogan